NATURAL ZEOLITE ACTIVATION AND ZAA/Ni CATALYST SYNTHESIS USING THE WET IMPREGNATION METHOD: AKTIVASI ZEOLIT ALAM DAN SINTESIS KATALIS ZAA/Ni MENGGUNAKAN METODE IMPREGNASI BASAH - Elsa Regita Hutami; Esmar Budi; Saddam Husin; Dita Adi Saputra; Muhammad Dikdik Gumelar (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
Zeolite has been widely used as a heterogeneous catalyst in catalytic cracking reactions. The role of zeolite as a catalyst depends on the amount and site of acid present on the surface of the catalyst. The imposition of nickel metal on the pores of zeolite can increase the surface area of the catalyst, which allows more reactant molecules to interact with the active site, thereby increasing the selectivity of the product. This study aims to study the process of natural zeolite activation and the manufacture of catalysts made from nickel-impregnation active natural zeolite consisting of BET and XRF characteristics. The zeolite used in this study is natural zeolite from Sukabumi. The catalyst variations used are activated natural zeolite with H2SO4 (ZAA) and ZAA/Ni with a nickel concentration of 2%. The type of nickel used is NiSO4 MHP (Mixed Hydroxide Precipitate) 2%. The results of the study showed an increase in the surface area of natural zeolite from 61.59 m2/g to 91.72 m2/g. Activation of zeolite using sulfuric acid has succeeded in reducing the impurity elements contained in natural zeolites such as Na, K, Cl, Mg and Fe. Nickel that has been successfully impregnated into zeolite pores by 0.30% in the ZAA/Ni catalyst.